Quarterly National Accounts Manual : Concepts, Data Sources, and Compilation - Maehle, Nils (Manuals and Guides, 2003)
This Manual provides guidance to compilers of national accounts on the concepts, data sources, and compilation methods required for development of a system of quarterly national accounts. More and more countries are recognizing that quarterly national accounts are an essential tool for management and analysis of their economy. The Manualis intended particularly for compilers who already have a knowledge of annual national accounting concepts and methods, and provides techniques for the development of a consistent time series of annual and quarterly accounts. It serves as acomplement to the System of National Accounts 1993, which has only a limited discussion of quarterly accounts, and will also prove useful as a tool for sophisticated users of quarterly national accounts.